Analisis Faktor-Faktor Kualitas Hidup Pasien Pasca-Stroke - Ni Putu Ayu Mawar Ariasih; Ni Luh Putu Thrisna Dewi; Ni Luh Putu Dewi Puspawati (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2025)
Introduction: Stroke is a leading cause of disability and death worldwide and a significant health problem in Indonesia, affecting various aspects of life. The overall impact of stroke is not limited to physical aspects but also includes psychological, social, and environmental dimensions, all of which contribute to the decline in the quality of life of post-stroke patients. The decline in quality of life among stroke patients is a serious concern as it plays an essential role in determining their survival and well-being. Objectives: This study aims to analyze the factors affecting the quality of life of post-stroke patients at the Neurology Clinic of RSUD Tabanan. Methods: This research uses a descriptive correlational design with a quantitative approach. The sample consists of 36 post-stroke patients at the Neurology Clinic of RSUD Tabanan. Data were collected using the SS-QOL questionnaire with a non-probability sampling technique, specifically purposive sampling. Data analysis was performed using the Chi-Square test. Results: The results show that the quality of life of most post-stroke patients at the Neurology Clinic of RSUD Tabanan falls within the good category, accounting for 77.8% (28 patients). Among the 12 characteristic factors analyzed, only age shows a significant relationship with the quality of life of post-stroke patients at the Neurology Clinic of RSUD Tabanan (p = 0.001). Conclusions: Age is significantly related to the quality of life of post-stroke patients compared to other factors. Age influences the quality of life of post-stroke patients due to its association with physiological factors, such as the body's recovery ability and susceptibility to complications, as well as social aspects, such as individual roles and responsibilities